Maturity Level Analysis of Inventory Information Systems Using COBIT 4.1 Framework at PT. MEDISTA UTAMA - Susi Susilowati (IJISTECH (International Journal of Information System and Technology), 2021)
PT. Medista Utama is a company engaged in the distribution of medical devices. We have implemented an information system in the inventory section that is used to control the movement of products in the company. The system used must be able to manage, convey and maintain information security properly. So it is necessary to carry out an audit that aims to evaluate the information system governance that is running and ensure that the existing procedures support the existing business processes in the company. The audits were conducted following the standards of the COBIT 4.1 Framework for IT governance. This study will focus on the Delivery Service and Support (DSS) domain to analyze several aspects of IT that are currently running in this company, from the level of system security used to the management carried out by the system. In this domain, the research is focused on the DS5, DS10, and DS11 sub-domains. From the research results it is known that DS5 is at the level of 1.3; DS10 and DS11 are at level 2 (Repetitive but Intuitive). The conclusion is the level of capability obtained from the inventory information system of PT. Medista Utama is still below the expected level. And many improvements are needed to maximize the company's performance to achieve the expected Maturity Level value.